Edonerpic maleate prevents epileptic seizure during recovery from brain damage by balancing excitatory and inhibitory inputs - Katsuno, Yuki; Jitsuki, Susumu; Ota, Wataru; Yamanoue, Tomomi; Abe, Hiroki; Takahashi, Takuya (Frontiers in Neural Circuits, 2024)
Functional recovery from brain damage such as stroke is a plastic process in the brain. Excitatory glutamate α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) plays crucial roles on neuronal functions, and synaptic trafficking of AMPAR is a fundamental mechanism of synaptic plasticity. We have recently identified collapsin-response-mediator-protein 2 (CRMP2)-binding compound, edonerpic maleate, which augments rehabilitative training dependent functional recovery from brain damage by the facilitation of experience driven synaptic delivery of AMPARs. The animals recovered from cryogenic brain injury possessed a potential compensatory area nearby injured region, where injection of CNQX, the antagonist of AMPARs, attenuated the functional recovery. Both excitatory and inhibitory synaptic inputs were enhanced at pyramidal neurons in the compensatory brain area of recovered animals from cryogenic injury by the administration of edonerpic maleate, while those of recovered animals without the drug exhibited augmentation of only excitatory synaptic input. The threshold of picrotoxin-induced epileptic seizure in recovered animals without edonerpic maleate treatment was lower than intact animals and recovered animals with edonerpic maleate. Thus, edonerpic maleate enhances motor function recovery from brain damage by balancing excitatory and inhibitory synaptic inputs, leading to the prevention of epileptic seizure during recovery.